Melatonin and tadalafil treatment improves erectile dysfunction after spinal cord injury in rats. (April 2014) - Tavukçu, Hasan Hüseyin; Şener, Tarik Emre; Tinay, İlker and Akbal, Cem and Erşahin, Mehmet and Çevik, Özge and Çadırcı, Selin and Reiter, Russel J and Şener, Göksel
Summary Oxidative stress plays an important role both in spinal cord injury (SCI) and erectile dysfunction (ED). The present study investigated the effects of melatonin and tadalafil treatment alone or in combination on SCI‐induced ED. Male Wistar albino rats (n = 40) were divided into five groups: sham‐operated control and SCI‐injured rats given either vehicle, melatonin (10 mg/kg, i.p.), tadalafil (10 mg/kg, p.o.) or a combination of melatonin and tadalafil. Spinal cord injury was induced using a standard weight‐drop method. On Day 7 after SCI, intracavernosal pressure (ICP) was measured and all rats were decapitated. Cavernosal tissues were obtained to examine caspase 3, nitric oxide synthase (NOS), myeloperoxidase (MPO) and superoxide dismutase (SOD) activities, as well as cGMP, nerve growth factor (NGF), malondialdehyde (MDA) and glutathione (GSH) levels. Spinal cord injury caused oxidative damage, as evidenced by increases in MDA and cGMP levels. In addition, MPO and caspase 3 activites were increased after SCI, whereas GSH and NGF levels and SOD activity were reduced. Melatonin effectively reversed these oxidative changes. Furthermore, in rats treated with both melatonin and tadalafil, the recoveries were more pronounced than in rats given either melatonin or tadalafil alone. The ICP/mean arterial pressure value in vehicle‐treated SCI rats was significantly higher than in the control group, whereas in the tadalafil‐ and tadalafil + melatonin‐treated groups have returned this value had returned to control levels. As an individual treatment, and especially when combined with tadalafil, a well‐known agent in the treatment of ED, melatonin prevented SCI‐induced oxidative damage to cavernosal tissues and restored ED, most likely due to its anti‐oxidant effects.